Patterns and ecological drivers of ocean viral communities - Brum, Jennifer R.; Ignacio-Espinoza, J. Cesar; Roux, Simon; Doulcier, Guilhem; Acinas, Silvia G.; Alberti, Adriana; Chaffron, Samuel; Cruaud, Corinne; Vargas, Colomban de; Gasol, Josep M.; Gorsky, Gabriel; Gregory, Ann C.; et al. (Science, 2015)
Viruses influence ecosystems by modulating microbial population size, diversity, metabolic outputs, and gene flow. Here, we use quantitative double-stranded DNA (dsDNA) viral-fraction metagenomes (viromes) and whole viral community morphological data sets from 43 Tara Oceans expedition samples to assess viral community patterns and structure in the upper ocean. Protein cluster cataloging defined pelagic upper-ocean viral community pan and core gene sets and suggested that this sequence space is well-sampled. Analyses of viral protein clusters, populations, and morphology revealed biogeographic patterns whereby viral communities were passively transported on oceanic currents and locally structured by environmental conditions that affect host community structure. Together, these investigations establish a global ocean dsDNA viromic data set with analyses supporting the seed-bank hypothesis to explain how oceanic viral communities maintain high local diversity.